Kajian Toksisitas Ekstrak Tumbuhan Talinum triangulare (Jacq) Willd. - Rustam, Erlina; Masri, Machdawaty; Arifin, Helmi (Jurnal Sains dan Teknologi Farmasi, 2011)
Toxicity studies have been conducted from plant extracts of Talinum triangulare (Jacq) Willd. on male white mice. Toxic effects were observed in the form of liver dysfunction and renal dysfunction of experimental animals that were given orally by the variation extract dose of 150, 300 and 600 mg / kg once daily for 15, 30 and 45 days. As a control group used male white mice which were given only 2.5% Tween 80. Parameters to be measured are the activity of SGPT and SGOT, creatinine clearance, renal function and percentage ratio of kidney weight. From the results of studies it appears that administration of plant extract Talinum triangulare (Jacq) Willd. with a given dose affects liver function and kidney function were significantly (P <0.05)